Modified Warden procedure using aortic homograft for superior vena caval translocation: Where is the evidence?. Issue 12 (11th October 2022) - Williams, Ian M.; Jubouri, Matti; Bailey, Damian M.; Bashir, Mohamad
Abstract: Background: Partial anomalous pulmonary venous connection (PAPVC) occurs when at least one pulmonary vein drains into the right atrium or its tributaries rather than the left atrium, most commonly connecting with the superior vena cava (SVC). The Warden procedure involves transecting the SVC proximal to the uppermost connection of the pulmonary vein followed by proximal SVC reattachment to the right atrial appendage. However, descending thoracic aortic homograft replacement for SVC translocation has recently been introduced as a modified technique. Aims: This commentary aims to discuss the recent study by Said et al. who reported their experiences with six PAPVC cases undergoing a modified Warden procedure using thoracic aortic homograft SVC translocation. Methods: A comprehensive literature search was performed using multiple electronic databases to collate the relevant research evidence. Results: The Warden procedure is associated with a 10% incidence of SVC obstruction with many requiring reintervention. Meanwhile, using the aortic homograft for SVC translocation, Said et al. observed no SVC obstructions. In addition, this modified technique does not require anticoagulation and has demonstrated an improvement in long‐term SVC patency. Nevertheless, it can be considered an expensive procedure. Moreover, since the thoracic aortic homograft utilized is biological tissue, only long‐term follow‐up will determine whether calcification and graft degeneration is an issue. Conclusion: It can be concluded that the modified Warden procedure is a safe and effective method to reconstruct the systemic venous drainage into the right atrium when a direct anastomosis under tension might be prone to re‐stenosis.